Dysfunctions of Public Administration System: Analysis of Institutional Reforms - Osipov, Vladimir S.; Skryl, Tatiana V.; Blinova, Ekaterina A.; Kosov, Michael E. (International Review of Management and Marketing, 2017)
The article dwells upon the major trends of public administration system development. The basic reasons for public administration inefficiency, dysfunctions of public administration system and prevailing lines of institutional reform are considered. The article provides an analysis of system dysfunctions. The article describes an interdisciplinary approach to the issue of public administration system creation and its functional unit's identification that possess various competencies and authorities in the planning horizon. The article determines the necessity of establishing a special government body responsible for strategy development and implementation of structural reforms. Keywords: public administration, competition, competitiveness, institutions, state budget. JEL Classifications: D2, H1, O2